2011
DOI: 10.2139/ssrn.1836905
|View full text |Cite
|
Sign up to set email alerts
|

'Where Ignorance is Bliss, 'Tis Folly to Be Wise': Transparency in Contests

Abstract: Increasingly, lobbying groups are subject to transparency requirements, obliging them to provide detailed information about their business. We study the effect this transparency policy has on the nature of lobbying competition. Under mild conditions, mandated transparency leads to an increase in wastefulness of lobbying competition and a decline in expected allocative efficiency. Hence we identify a negative side-effect of transparency policy, which also has implications for various other fields such as politi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Denter et al . () obtained the same result by comparing no and full disclosure . Our analysis demonstrates that their result is robust if more sophisticated disclosure policies are allowed in the contest organiser's choice.…”
Section: Bayesian Persuasionsupporting
confidence: 55%
See 3 more Smart Citations
“…Denter et al . () obtained the same result by comparing no and full disclosure . Our analysis demonstrates that their result is robust if more sophisticated disclosure policies are allowed in the contest organiser's choice.…”
Section: Bayesian Persuasionsupporting
confidence: 55%
“…Denter et al . () compare full disclosure and no disclosure with binary valuations. In our framework with N ≥ 2, it can be shown that full disclosure dominates no disclosure if and only if the commonly known contestant's valuation is above a cut‐off…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our paper is also related to the literature on players' incentive to acquire and share information in different auction formats, such as Persico (), Yildirim (), Compte and Jehiel (), Szech (), Morath and Münster (), Denter, Morgan, and D. Sisak (), and Kovenock, Morath, and Münster (). In particular, in contrast to this paper, Denter, Morgan, and Sisak () consider one‐sided asymmetric information in an all pay setting.…”
mentioning
confidence: 99%